Early versus delayed thromboprophylaxis with LMWH in pelvic-acetabular trauma- a prospective study. Issue 2 (February 2022) - Shetty, Akshay; Aggarwal, Sameer; Patel, Sandeep; Sharma, Siddharth; Jindal, Karan; Prakash, Mahesh
Highlights: Early versus delayed thromboprophylaxis with LMWH in pelvic-acetabular trauma. Delayed presentation of pelvic-acetabular fractures is a common scenario in developing countries and there is usually a delay of more than 24 h in their presentation. There was no difference between early and delayed thromboprophylaxis with LMWH in pelvic-acetabular trauma. Abstract: Background: Delayed presentation of pelvic-acetabular fractures is a common scenario in developing countries and there is usually a delay of more than 24 h in their presentation. Objectives: We aim to comparatively analyse early(<24 h) versus delayed (>24 h) thromboprophylaxis with low molecular weight heparin (LMWH) in prevention of deep venous thrombosis (DVT) in Pelvic Acetabular fractures. Methods: Patients of pelvic-acetabular fractures who presented during 1 year of study period were divided into 2 groups after exclusion of patients with contraindications for thromboprophylaxis. Group A included patients who received LMWH prophylaxis within 24 h of injury. Group B included patients who received LMWH prophylaxis after 24 h of injury. All patients underwent CT venography at day 14 and were followed up with doppler ultrasound on 4th and 8th week. Results: 110 patients with pelvic-acetabular fractures were included after exclusion of 61 patients. 4 out of 29 patients in group A (13.8%) and 12 out of 81 patients (14.8%) in group B developed DVT. There was no significant difference in incidence of DVT between Group A and B (P value-0.893). Conclusion: There was no difference between early and delayed thromboprophylaxis with LMWH in pelvic-acetabular trauma.